Formulation and Evaluation of Immediate Release Telmisartan Tablets using Hydrophilic Polymers - Swati, S. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Telmisartan is an anti-hypertensive drug under the class of angiotensin II receptor blocker. The aim is to formulate and evaluated immediate release telmisartan tablets using hydrophilic polymers. Materials and Method: The hydrophilic polymers are polyethylene glycol 4000 (PEG-4000) and PEG-6000. Solid dispersion is prepared with polymers with different ratios 1:0.5, 1:1, 1:2 and formulated into tablets. Formulations were characterized for drug content studies, drug release studies, and drug-polymer interactions using Fourier transform infrared spectroscopy (FTIR) spectrum. Results and Discussions: Formulation containing 1:2 ratio of drug: PEG-6000 showed the best release with a cumulative release of 99.67% as compared to 74.36% for the PEG-4000. The FTIR studies showed that there is no interaction between the drug and polymer. Conclusion: Based evaluation of different parameters it was concluded that formulation of immediate release tablets of telmisartan was successfully done and F6 shows 100% at 60 min.